Temporal separation between CO2 assimilation and growth? Experimental and theoretical evidence from the desiccation-tolerant moss Syntrichia ruralis - Royles, Jessica (The New phytologist, 2013)
© 2013 The Authors. New Phytologist © 2013 New Phytologist Trust.